2009
DOI: 10.1007/s12185-009-0259-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding rituximab to CHOP-based therapy on clinical outcomes for Japanese patients with diffuse large B-cell lymphoma: a propensity score matching analysis

Abstract: We conducted a retrospective analysis to evaluate the impact on clinical outcomes of adding rituximab to cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) treatment for diffuse large B-cell lymphoma (DLBCL) patients in Japan. A propensity score method was used to compensate for the non-randomized study design. From January 2000 to December 2004, 378 patients who were newly diagnosed with DLBCL at 13 institutes were enrolled: 123 in the rituximab plus CHOP-based chemotherapy (R+) group, and 255 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…There was no significant difference in patients who had been treated with R-CHOP like therapy compared to those who were treated with CHOP-like chemotherapy without rituximab. These results are in contrary to many other published results (Coiffer et al, 2002;Feugier et al, 2005;Sehn et al, 2005;Pfreundschuh et al, 2006;Nishimori et al, 2009). The most likely explanation for this would be the inadequate dose of rituximab.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There was no significant difference in patients who had been treated with R-CHOP like therapy compared to those who were treated with CHOP-like chemotherapy without rituximab. These results are in contrary to many other published results (Coiffer et al, 2002;Feugier et al, 2005;Sehn et al, 2005;Pfreundschuh et al, 2006;Nishimori et al, 2009). The most likely explanation for this would be the inadequate dose of rituximab.…”
Section: Discussioncontrasting
confidence: 99%
“…The results from European Groupe D'Estude des Lymphomes des L'Adulte LNH-98-5 study (GELA) study demonstrated that 5 year overall survival (OS) is significantly higher in elderly patients with rituximab combination chemotherapy (Coiffer et al, 2002). In younger patients who had R-CHOP like chemotherapy had an increased 3-year event-free survival and OS compared to those without rituximab; 79% vs 59% and 93% vs 84% respectively (Pfreundschuh et al, 2006) More recently, the Asia groups including the Japanese, Korean, Chinese and Singaporean had also confirmed similar findings in patients with DLBCL (Park et al, 2006;Li et al, 2007;Ngo et al, 2008;Nishimori et al, 2009;Seiki et al, 2010). However, within the Asian countries, there are many which have limited health care resources in treating patients with lymphoma.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…[13][14][15] Since the introduction of rituximab, several prognostic factors have been reevaluated in DLBCL patients, [16][17][18] but the prognostic value of HCV infection in rituximab combination chemotherapy has not been well established. In addition, hepatitis B virus (HBV) reactivation is a well-documented complication that occurs frequently after introduction of rituximab.…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor effect of rituximab is mediated by antibody‐dependent cell‐mediated cytotoxicity (ADCC), complement‐dependent cytotoxicity (CDC), antibody‐mediated phagocytosis of tumor cells and rituximab‐induced apoptosis . Several trials have demonstrated that the addition of rituximab to conventional chemotherapy improved the response rate and prolonged the survival of DLBCL patients . Therefore, rituximab is included in the R‐CHOP, R‐EPOCH, R‐ESHAP and R‐GEMOX regimens recommended for DLBCL treatment .…”
mentioning
confidence: 99%